2015
DOI: 10.1136/bcr-2015-211312
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal pharyngitis: an uncommon cause of subdural empyema

Abstract: A 7-year-old girl with an unremarkable medical history presented to a local paediatric emergency department with a 7-day history of fever, sore throat and vomiting, and a 1-day history of rash. She was admitted to the hospital, with presumed Kawasaki disease. A few hours after admission, the patient had sudden onset of two witnessed tonic-clonic seizures and subsequent decreased mental status. She was transferred to the paediatric intensive care unit and started on broad-spectrum antibiotics. On hospital day 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is important to emphasize that ESD caused by a pharyngitis is rare. A prior study showed ESD related to pharyngitis in a 7-year-old child with a 7-day fever, even though the etiologic agent was Streptococcus pyogenes 18 . In contrast with our study, one can isolate Peptostreptococcus sp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is important to emphasize that ESD caused by a pharyngitis is rare. A prior study showed ESD related to pharyngitis in a 7-year-old child with a 7-day fever, even though the etiologic agent was Streptococcus pyogenes 18 . In contrast with our study, one can isolate Peptostreptococcus sp.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of ESD is medical and surgical; medically, it consists of using broad-spectrum antibiotics, like third-generation cephalosporins, carbapenems and metronidazole 18 - 20 , more efficient to treat aerobic agents than aerobic ones, during three to four weeks post-surgical drainage. This regimen contrasts with the treatment that is established for the patient prescribed with meropenem, metronidazole and vancomycin, although the latter is recommended to treat ESD before surgeries or after trauma due to the presumption of microbial contamination 1 , 6 .…”
Section: Discussionmentioning
confidence: 99%
“…They found that Streptococcus triggered an inflammatory response and resulted in the development of a neurological condition. There are no published data on the association of Streptococcus with ACM, but several studies have linked this species with other neurological complications such as Sydenham’s chorea [ 13 ], meningitis [ 9 ], abscesses [ 11 ], empyema [ 10 ], and sepsis-associated encephalopathy [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial cause of pharyngitis is frequently associated with post-streptococcal glomerulonephritis, acute rheumatic fever, and rheumatic heart disease [7,8]. Although a few case reports have been published on the possible association between strep pharyngitis and intracranial infections [9][10][11], the role of microbial infection in ACM is not clear. To date, several cases have reported patients with brain empyema, brain abscess, and meningoencephalitis who have been infected with strep throat, but no data have been published on the onset of clinical manifestations of ACM after strep pharyngitis.…”
Section: Introductionmentioning
confidence: 99%